Energy Use of the Solid-Phase Product of Oil Sludge Waste Thermal Conversion; AIP Conference Proceedings; Vol. 2422 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2021) - Larionov K. B. Kirill Borisovich; Kaltaev A. Albert; Tabakaev R. B. Roman Borisovich; Melnik G. S. Gulnara; Zenkov A. V. Andrey Viktorovich (Heat and mass transfer in combustion technology, 2021)
Title screen